Bio-conversion of methane to liquid transportation fuel using methanotrophic bacteria - Stead, Christopher Edward (2019)
Methane is the second largest contributor to climate radiative warming with a global warming potential of ~34 times greater than that of carbon dioxide. Capturable methane from anthropogenic sources includes mainly natural gas and bio-gas and represents a flux of around 162 Mt yr-1. Methane is often flared or vented due to difficulties with storage and transportation. Conversion technologies have poor scalability so are not viable at small or geographically isolated methane sources. It is envisaged that microbial bio-conversion of methane using methane oxidising bacteria (methanotrophs) can be used to biologically upgrade methane to liquid transportation. The present study set out to develop and explore a scalable bioconversion technology for conversion of methane to liquid transportation fuel. To do this an end-to-end approach was taken than included isolation of environmental methanotrophs, characterisation of isolates and metabolic engineering of isobutanol biosynthesis. Using bacterial isolation techniques such as extinction dilution plating and miniaturised extinction dilution methanotrophs were isolated from a variety of methane rich environmental samples such as freshwater sediment, soil and manure. These methanotrophic isolates were characterised and identified within established genera/species of which some are suspected to be novel species. Type I isolates included: Isolate 01; Methylocystis sp., isolate 03; Methylocystis sp., isolate 3*; Methylocystis nov sp. and isolate 6; Methylocystis SB2. Novel characteristics of the Methylocystis genus such as fimbriae were viewed using TEM in isolate 3*. Type I isolates included, isolate 14 Methylococcus capsulatus (isolated from the same sampling site as the type strain Methylococcus capsulatus (Bath)) and isolate 10 Methylocaldum nov sp. of which isolate 10 exhibited novel characteristics for the genus. Isolate 14 and 6 had their genome sequenced using a PacBio method and genomes were compared to closely related established strains genomes including Methylocystis rosea and Methylococcus capsulatus (Bath). Isolate 14 and isolate 6 were chosen for engineering and A molecular toolbox was developed including expression vectors, promoters and selection markers to facilitate the metabolic engineering of isolates and established strains. In addition to this an attempt was made to knockout carbon storage production within the isolates via allelic exchange. Metabolic engineering of an isobutanol biosynthetic pathway was employed by diverting flux from native valine biosynthesis to isobutanol. To do this a selection of heterologous keto-acid decarboxylases and alcohol dehydrogenases were overexpressed which, along with 2-ketoisovalerate feeding, yielded an isobutanol titre of 0.53 mM in M. parvus, 0.117 mM in M. capsulatus (Bath) and 0.27 mM in isolate 6 (Methylocystis SB2).